Studying Abroad Narrative Imaginaries: North and South Europe - Pierluca Birindelli (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
Through analysis of 50 autoethnographies I interpret international students’ imaginaries of Italy-Florence (South Europe), Finland-Helsinki (North Europe) and what can be called “the cosmopolitan elsewhere”. International students’ imaginary of Finland-Helsinki is very slight; that of Italy-Florence is richer and variously articulated: media images and narratives shape students’ expectations before their arrival in the host country. The Finland-Helsinki country profile is instead associated with a vague idea of Northern Europe and often confused with Scandinavia. The respective autoethnographic passages can be synthetically interpreted as past (Italy) vs. present (Finland). On one side Italy-Florence’s image is almost embedded in a cultural past, on the other Finland-Helsinki’s image is almost severed from its history and is seen more as a geographical entity: the deep and mysterious north. Analysis of secondary sources connected with studying abroad reveals the absence of a clear-cut narrative of what it means to be an international student. Nevertheless, there is a glimpse of a vague cosmopolitan narrative. This story, constructed on a global scale by different actors and institutions upholds the generic validity of studying abroad for both instrumental and expressive reasons, and sees it as an institutionalized rite of passage towards global citizenship.